Alcohol and marijuana use among young injured drivers in Arizona, 2008–2014 - Shults, Ruth A. (Traffic Inj Prev, 2019)
OBJECTIVE: We examined alcohol and marijuana use among injured drivers aged 16–20 years evaluated at Arizona level 1 trauma centers during 2008–2014. METHODS: Using data from the Arizona State Trauma Registry, we conducted a descriptive analysis of blood alcohol concentration (BAC) and qualitative test results (positive or negative) for delta-9-tetrahydrocannabinol (THC) by year of age, sex, race, ethnicity, injury severity, seat belt use, motorcycle helmet use, and type of vehicle driven. To explore compliance with Arizona’s motorcycle helmet law requiring helmet use for riders <18 years old, we examined helmet use by age. RESULTS: Data on 5,069 injured young drivers were analyzed; the annual number of injured drivers declined by 41% during the 7-year study period. Among the 76% (n=3,849) of drivers with BAC results, 19% tested positive, indicating that at least 15% of all drivers had positive BACs. Eightytwo percent of the BAC-positive drivers had BACs ≥0.08 g/dL, the illegal threshold for drivers aged ≥21 years. Among the 49% (n=2,476) of drivers with THC results, 30% tested positive, indicating that at least 14% of all drivers were THC-positive. American Indians and blacks had the highest proportion of THC-tested drivers with positive THC results (38%). In addition, 28% of tested American Indians had positive results for both substances, more than twice the proportion seen in all other race or ethnic groups. Crude prevalence ratios suggested that drivers who tested positive for alcohol or THC were less likely than those who tested negative to wear a helmet or seat belt, further increasing their injury risk. Helmet use among motorcyclists was lower among 16- and 17-year-old riders compared to 18- to 20-year-olds, despite Arizona’s motorcycle helmet law requiring riders aged <18 years to wear a helmet. CONCLUSIONS: About 1 in 4 injured drivers aged 16–20 years tested positive for alcohol, THC, or both substances. Most drivers with positive BACs were legally intoxicated (BAC ≥0.08 g/dL). All substance-using young drivers in this study were candidates for substance abuse screening and possible referral to treatment. Broader enforcement of existing laws targeting underage access to alcohol and alcohol-impaired driving could further reduce injuries among young Arizona drivers. To further reduce crash-related injuries and fatalities among all road users, the state could consider implementing a primary enforcement seat belt law and a universal motorcycle helmet law.